2022
DOI: 10.1007/s12144-022-02863-z
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of cosmetic surgery in adolescents: The effects of caregiver eating messages and objectified body consciousness

Abstract: Cosmetic procedures are aimed at enhancing clients’ attractiveness by modifying their physical appearance. Women prefer cosmetic surgery more than men do, due to the ideal of leanness advertised by the media. Female adolescents, undergoing an emotionally unstable developmental stage, are particularly responsive to unrealistic beauty standards. The more they internalize cultural norms, the more they objectify their bodies. Young people’s views on their bodies are essentially influenced by the feedback received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…The results showed that self-objectification was correlated with cosmetic surgery consideration of young women, indicating that young women with a higher degree of self-objectification were more likely to use cosmetic surgery as a body image coping strategy. The finding was consistent with previous research results (Őry et al, 2023;Sun, 2018Sun, , 2021Vaughan-Turnbull and Lewis, 2015). The female college students in this study scored lower for their cosmetic surgery consideration than in other studies (Li and Xiao, 2023;Sun, 2021); this may be because males were not present during the measurement process of this study, which controlled for the effect of state self-objectification on cosmetic surgery consideration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that self-objectification was correlated with cosmetic surgery consideration of young women, indicating that young women with a higher degree of self-objectification were more likely to use cosmetic surgery as a body image coping strategy. The finding was consistent with previous research results (Őry et al, 2023;Sun, 2018Sun, , 2021Vaughan-Turnbull and Lewis, 2015). The female college students in this study scored lower for their cosmetic surgery consideration than in other studies (Li and Xiao, 2023;Sun, 2021); this may be because males were not present during the measurement process of this study, which controlled for the effect of state self-objectification on cosmetic surgery consideration.…”
Section: Discussionsupporting
confidence: 92%
“…For example, researchers manipulated state self-objectification by leading female participants to believe they would be interacting with a man and confirmed that state self-objectification affects women's cosmetic surgery consideration (Calogero et al, 2014). In this study, self-objectification explained more variance for cosmetic surgery consideration than that in previous studies (Őry et al, 2023;Sun, 2018;Vaughan-Turnbull and Lewis, 2015).…”
Section: Discussionsupporting
confidence: 61%
“…In relation to the acceptability of cosmetic procedures in relation to age and gender, a substantial number of respondents expressed the viewpoint that age and gender should not serve as restrictive criteria. The aforementioned discovery suggests a transition towards a viewpoint that is more encompassing and equitable towards cosmetic operations, which is in line with current societal principles of self-expression and independence [25,26]. Nevertheless, it is crucial to take into account that public attitudes could fluctuate across diverse cultural contexts, and additional investigation is required to delve deeper into these processes.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, the media indirectly orient individuals toward the available surgical means of meeting unrealistic beauty standards. 12 This study was conducted to assess the level of acceptance of cosmetic surgery among young Saudi women as well as the factors influencing their decisions.…”
Section: Introductionmentioning
confidence: 99%